The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2174/1574884712666170310111125
|View full text |Cite
|
Sign up to set email alerts
|

Dutasteride in Androgenetic Alopecia: An Update

Abstract: Like finasteride, dutasteride is now becoming popular treatment option in AGA, due to its good response shown by various randomized control studies and meta-analysis. Also, in most of these studies, dutasteride was found to be better than finasteride with comparable adverse effects. Therefore, dutasteride could become a treatment of choice for AGA in near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 0 publications
2
43
0
Order By: Relevance
“…Although hepatic metabolism mediated by CYP3A4 and CYP3A5 is well recognized as a major elimination pathway of DUT in humans [6,7], little information has been available as to the hepatic CYPs involved in the metabolism of DUT in rats. The in vitro microsomal metabolism data presented in this study revealed that the metabolism of DUT was markedly reduced by KET, a potent inhibitor of CYP3A in rats and humans ( Figures 6B and 7B) [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although hepatic metabolism mediated by CYP3A4 and CYP3A5 is well recognized as a major elimination pathway of DUT in humans [6,7], little information has been available as to the hepatic CYPs involved in the metabolism of DUT in rats. The in vitro microsomal metabolism data presented in this study revealed that the metabolism of DUT was markedly reduced by KET, a potent inhibitor of CYP3A in rats and humans ( Figures 6B and 7B) [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…DUT, a dual inhibitor of type-1 and type-2 5AR, was approved by the US Food and Drug Administration (FDA) in 2001 for the treatment of symptomatic benign prostatic hyperplasia [6]. Further, it was approved for androgenic alopecia in Korea and Japan [7]. Previous in vitro studies have shown that compared to finasteride, DUT more potently inhibited type-1 and type-2 5AR by 45-and 2.5-fold, respectively [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, administration of finasteride and dutasteride for androgenic alopecia might be viewed in two very different ways. Taking into account only its therapeutic efficiency for AGA, several authors have demonstrated that dutasteride (a stronger inhibitor/ more potent antiandrogen than finasteride) produces superior results in ameliorating androgenic alopecia than finasteride, such that it should be preferred in clinical practice for AGA (11).…”
Section: Discussionmentioning
confidence: 99%
“…While hair loss is a problem for many people, effective therapeutic agents for this condition are quite limited (1,2). Intensive efforts toward developing therapeutic chemical compounds have been made by analyzing the mechanisms underlying hair follicle development, regeneration, and induction of the telogen-to-anagen transition in mouse models (3,4).…”
mentioning
confidence: 99%